Answer:
Option D.
![G(x)=x^(3)-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/elzzqud22yrw12iouay57qq4w6jvtcdo9t.png)
Explanation:
we have
-----> the parent function
The vertex of the function F(x) is the origin (0,0)
The vertex of the function G(x) is the point (0,-1)
so
The rule of the translation is equal to
(x,y)------> (x,y-1)
That means ------> The translation is 1 unit down
Applying the rule of the translation to F(x)
F(x)-------> G(x)
![G(x)=x^(3)-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/elzzqud22yrw12iouay57qq4w6jvtcdo9t.png)